Use of Lipe® as External Indicator, Replacing the Total Collection for Measuring the Coefficients of Metabolization of Nutrients and Metabolizable Energy for Broilers - Miranda , D.J.A.; Lara, L.J.C.; Baiao, N.C.; Saliba, E.O.S.; Rocha, J.R.S.; Pompeu, M.A.; Andrade, R.C.; Cardeal, P.C. (International Journal of Poultry Science, 2013)
To evaluate the efficacy of the LIPE® as external marker to measure the digestibility of nutrients and Apparent Metabolizable Energy (AME) and apparent metabolizable corrected for nitrogen balance (AMEn) compared to the total collection method for broilers from one to 21 days and 22 to 42 days, 15 chicks one day old and 10 broilers with 22 days of age, respectively, in a randomized block design with two treatments and 24 repetitions, each repetition being considered as a block. There was no significant correlation (P>0.05) for the metabolizable coefficient of dry matter (MDM) for both phases. For the metabolizable coefficient of crude protein (MCP) in the initial phase, the correlation was median (between 30 and 70%), positive and significant (P<0.01), while for the metabolizable coefficient of ether extract (MEE) and AME and AMEn, the correlations were strong (above 70%), positive and significant (P<0.01), as well as to the MCP, MEE, AME and AMEn in the growth phase in which strong correlations were found (above 70%), positive and significant (P<0.01). When comparing the same variables using analysis of variance, depending on the methodology employed, there was no difference by F test (P>0.05) for MDM, MCP, MEE, AME and AME n for both phases, with the exception of AMEn in the initial phase, in which a higher value was observed (P<0.05) for LIPE®. It is concluded that the LIPE® as external indicator can be used to measure the production of excreta and subsequent determination of metabolization coefficient and energy values for broilers.